2010
DOI: 10.1136/adc.2008.148932
|View full text |Cite
|
Sign up to set email alerts
|

Valproate and risk of fracture in Rett syndrome

Abstract: The effect of valproate on bone health should be considered when managing epilepsy in Rett syndrome. Multiple mechanisms could be contributing to this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
0
19
1
1
Order By: Relevance
“…No specific medications are contraindicated in Rett syndrome; however, the issue of bone health is an important consideration when prescribing anti-seizure drugs. One study found increased risk of fracture in Rett syndrome associated with valproate use, whereas another study demonstrated that low vitamin D levels, common in Rett syndrome, were not associated with anti-seizure drug use (Leonard et al, 2010;Motil et al, 2011). In summary, when seizures are concluded to be epileptic in origin and anti-seizure drugs are initiated, the side effect profiles of medications should be considered carefully, and medications, which can cause behavioural issues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…No specific medications are contraindicated in Rett syndrome; however, the issue of bone health is an important consideration when prescribing anti-seizure drugs. One study found increased risk of fracture in Rett syndrome associated with valproate use, whereas another study demonstrated that low vitamin D levels, common in Rett syndrome, were not associated with anti-seizure drug use (Leonard et al, 2010;Motil et al, 2011). In summary, when seizures are concluded to be epileptic in origin and anti-seizure drugs are initiated, the side effect profiles of medications should be considered carefully, and medications, which can cause behavioural issues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the largest study to date to describe this mutation and the sample size has allowed use of appropriate statistical methods including survival analysis. Our case studies also use information collected at multiple time points, 14 and questionnaire data has been supplemented with observed video data of functional abilities that had been collected on two occasions. 19,33,36 Longitudinal data from different perspectives were able to provide depth to the description of our case studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additional questionnaire data have been collected every 2 to 3 years since 2000. 14 InterRett was established in 2003 15 and cases are ascertained through a variety of sources including parent support groups, the listserv Rettnet and also bulk submission of de-identified data provided by clinicians outside Australia from countries such as Spain, France, Israel and Canada. InterRett questionnaires are completed online by families and clinicians at one time point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D status) environmental and genetic risk factors. Risk factors for fractures such as genotype 173 and use of certain anti-epileptic medications 181 did not always correlate exactly with those for low bone density, which also varied by outcome parameter and body site. For example, right femoral neck areal bone mineral density was particularly impaired with increasing age and lack of mobility in comparison to other parameters.…”
Section: Bone Healthmentioning
confidence: 99%